The effects of surfactants on plunging breakers - Erinin, M; Liu, C; Liu, X; Mostert, W; Deike, L; Duncan, J (Cambridge University Press, 2023)
The effects of surfactants on a mechanically generated plunging breaker are studied experimentally in a laboratory wave tank. Waves are generated using a dispersively focused wave packet with a characteristic wavelength of λ0 = 1.18 m. Experiments are performed with two sets of surfactant solutions. In the first set, increasing amounts of the soluble surfactant Triton X-100 are mixed into the tank water while in the second set, filtered tap water is left undisturbed in the tank for wait times ranging from 15 minutes to 21 hours. Increasing Triton X-100 concentrations and longer wait times lead to surfactant-induced changes in the dynamic properties of the free surface in the tank. It is found that low surface concentrations of surfactants can dramatically change the wave breaking process by changing the shape of the jet and breaking up the entrained air cavity at the time of jet impact. Direct numerical simulations (DNS) of plunging breakers with constant surface tension are used to show that there is significant compression of the free surface near the plunging jet tip and dilation elsewhere. To explore the effect of this compression/dilation, the surface tension isotherm is measured in all experimental cases. The effects of surfactants on the plunging jet are shown to be primarily controlled by the surface tension gradient (ΔE) while the ambient surface tension of the undisturbed wave tank (σ0) plays a secondary role.